Countdown to 2015: a decade of tracking progress for maternal, newborn, and child survival. Issue 10032 (14th May 2016) - Victora, Cesar G; Requejo, Jennifer Harris; Barros, Aluisio J D; Berman, Peter; Bhutta, Zulfiqar; Boerma, Ties; Chopra, Mickey; de Francisco, Andres; Daelmans, Bernadette; Hazel, Elizabeth; Lawn, Joy; Maliqi, Blerta; et al.
Summary: Conceived in 2003 and born in 2005 with the launch of its first report and country profiles, the Countdown to 2015 for Maternal, Newborn, and Child Survival has reached its originally proposed lifespan. Major reductions in the deaths of mothers and children have occurred since Countdown's inception, even though most of the 75 priority countries failed to achieve Millennium Development Goals 4 and 5. The coverage of life-saving interventions tracked in Countdown increased steadily over time, but wide inequalities persist between and within countries. Key drivers of coverage such as financing, human resources, commodities, and conducive health policies also showed important, yet insufficient increases. As a multistakeholder initiative of more than 40 academic, international, bilateral, and civil society institutions, Countdown was successful in monitoring progress and raising the visibility of the health of mothers, newborns, and children. Lessons learned from this initiative have direct bearing on monitoring progress during the Sustainable Development Goals era.